The expanding landscape of online education: Who engages and how they fare - Lisa Barrow; Wesley Morris; Lauren Sartain (Federal Reserve Bank of Chicago, 2022)
Online offerings at traditional brick-and-mortar universities have become common, though some question if online courses can adequately substitute for the in-person college experience. We explore changes in undergraduate online course enrollment at a large, public 4-year system and the impacts of online courses on student outcomes. Online enrollment in courses nearly doubled from 2012 to 2019 when almost 40 percent took at least one class online. Female students and older students were especially likely to take online classes. Using an instrumental variables approach, we find that GPAs are higher in the terms when students take at least one class online. However, we do not find evidence that online course taking results in increased degree completion. While online course offerings offer students flexibility, those who take online courses may need additional advising for online learning to translate into higher rates of graduation.
Keywords: I21; I23; 330; higher education; education quality; online education; educational attainment; student achievement